Interplay between endogenous hormones and immune systems in human metapneumovirus pathogenesis and management - Ruiz-Pozo, Viviana A.; Cadena-Ullauri, Santiago; Tamayo-Trujillo, Rafael; Guevara-Ramírez, Patricia; Paz-Cruz, Elius; Castañeda Cataña, Mayra A.; Zambrano, Ana Karina (Frontiers in Pharmacology, 2025)
The present review explores the role of endogenous hormones, such as cortisol, melatonin, thyroid hormones, sex hormones, and insulin, in the modulation of the immune response to a human metapneumovirus (hMPV) infection. hMPV is a respiratory pathogen responsible for severe infections, particularly in vulnerable populations like children and the elderly. The virus triggers inflammatory responses through various molecular processes, including cytokine production and immune signaling pathways. Notably, these processes can be influenced by endocrine factors, such as hormones. Cortisol, through hypothalamic-pituitary-adrenal (HPA) axis activation, modulates inflammation but may contribute to immunosuppression. Melatonin inhibits the NLRP3 inflammasome, reducing lung inflammation. Thyroid hormones regulate immune responses via nuclear factor kappa B (NF-κB) and JAK/STAT pathways, while hypothyroidism may alter infection severity. Sex hormones, particularly estrogens, enhance antiviral immunity, whereas androgens may have variable effects on immune modulation. Insulin influences inflammation through NF-κB suppression, with insulin resistance potentially worsening viral pathogenesis. Therapeutic implications suggest that modulating these hormonal pathways could aid in hMPV management. Strategies such as hormone therapy, glucocorticoid regulation, and nanoparticle-based drug delivery are potential routes of intervention. The aim of the present review is to understand the complex interplay between endogenous hormones and the immune system during an hMPV infection by describing the complex molecular mechanisms associated with these processes.